Dynamic analysis of breaking wave impact on a floating offshore wind turbine via smoothed particle hydrodynamics - Wang, Shengzhe; Chuang, Wei-Liang (Marine structures, 2025)
•SPH validated against breaking wave experiment impacting floating TLP.•Dynamics of DeepCwind FOWT subject to breaking and nonbreaking waves explored.•Largest forces attributed to breaking wave impinging rear columns of FOWT.•Wave breaking imparts significant accelerations to nacelle.•Maximum mooring tensions not significantly influenced by breaking wave. This work leverages Lagrangian smoothed particle hydrodynamics (SPH) to explore the structural and hydrodynamic response of floating offshore wind turbines (FOWT) subject to impulsive breaking waves. The SPH formulation was first validated against breaking wave impact on a model tension leg platform (TLP) which demonstrated good consistency with experimental results. Following validation, wave focusing was utilized to generate both breaking and nonbreaking extreme waves impacting a moored semi-submersible FOWT at full scale. Impulsive forces and accelerations resulting from the plunging breaker were observed to exceed that of nonbreaking waves by up to 70 % and 230 %, respectively, and were highly sensitive to the wave impingement location relative to the FOWT. However, wave breaking did not appear to significantly influence rigid body motions and yielded lower mooring tensions than its nonbreaking counterpart due to the short duration of impact. This work ultimately demonstrates the applicability of SPH for the simulation of breaking wave interactions with floating bodies and provides further impetus towards the study of FOWTs under such conditions.